Learning experiences of adult African American women at selected Midwest postsecondary institutions - Peck, Laura Content (Kansas State University, 2010)
This study examined how adult African American women experienced learning at two post-secondary institutions in the Midwest; a diverse, urban community college, and a predominantly white research university. The study also considered how barriers, challenges, responsibilities, and support systems impacted their learning experiences. Gender, race and age were variables of interest, and three theoretical lenses; Belenky, Clinchy, Goldberger and Tarule's Women's Ways of Knowing, McClusky's Theory of Margin/Adult Roles and Responsibilities, and Critical Race Theory were used to explore the participants' experience of learning. This topic was of interest due to the paucity of research conducted in the area of post-secondary institutions, with adult African American women in the Midwest. This study found that learners used active learning, linked their learning to their life experiences, encountered racism, experienced barriers; situational, institutional, dispositional, and information; utilized familial, instructor, peer and spiritual support systems, would benefit from career advising, and that career goal uncertainty was a common obstruction. The women participating in this research were determined, motivated and goal oriented, and served as role models for their children, sought education to improve their lives, and emphasized the importance of education to reach career and life goals.
Keywords: Midwest African American Women; Barriers and Challenges; Education, Adult and Continuing (0516)